Using Panel Co‐Integration Methods To Understand Rising Top Income Shares. Issue 284 (6th February 2013) - Neal, Timothy
<x xml:space="preserve">Abstract</x> Rising top income shares in developed countries have recently generated a great deal of political and economic discussion. While many theories have been proposed to explain this increase, there has been little robust econometric testing of those explanations. Using a variety of data sources, this study will employ panel co‐integration methods, including the FMOLS and PDOLS estimators, to understand the long‐run relationship between the top 1 per cent income share and a number of explanatory variables. Our analysis finds that economic openness, the size and ideology of government, the development of financial markets, top marginal tax rates, technological progress and the strength of unions are all important determinants of top income shares. These results offer a comprehensive explanation of why top income shares have been rising in a number of developed economies in the last three decades. The implications of the findings for economic and social policy are also discussed.